SUFISM ON THE SILVER SCREEN: Indonesian Innovations in Islamic Televangelism (JOURNAL OF INDONESIAN ISLAM, 2008)
As a carrier of Islam’s esoteric tradition, Sufism would seem to be an unlikely candidate for promoting Islamic piety in the popular mass media in Muslim majority societies of the twenty-first century. It is thus remarkable that several of the most sensationally popular of Indonesia’s new breed of televangelists have promoted Islam by modelling ‘Sufistik’ forms of intensified piety. This article examines the electronically-mediated mass predication programs of two of Indonesia’s best known televangelists, Abdullah Gymnastiar and M. Arifin Ilham. Both are recognised by the viewing public as ‘Sufistik’. The article identifies the elements of the Sufi tradition upon which the preachers draw. It also examines how those elements can be projected effectively on television to convey the intense spiritual intimacy with God which Muslims seek through Sufi devotions.